Ionic conductivity and electrochemical properties of polymer gel electrolyte using novel three-dimensional network polymer host composed of electrospun nanofibers - Tan, Li Tong. (2012)
The objective of this project is to prepare a novel three-dimensional polymer gel electrolyte and evaluate its ionic conductivity and electrochemical properties. The polymer gel electrolyte is based on varying composition of polyethylene oxide in the polymer blend of polyvinylidene fluoride (PVDF) and polyethylene oxide (PEO).